2015
DOI: 10.5194/acp-15-6971-2015
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide in the marine boundary layer over the South Atlantic during the OOMPH cruise in March 2007

Abstract: Abstract. In the OOMPH (Ocean OrganicsModifyingIn situ measurements of hydrogen peroxide, methylhydroperoxide and ozone were performed and are compared to simulations with the atmospheric chemistry global circulation model EMAC (ECHAM/MESSy Atmospheric Chemistry). The model generally reproduces the measured trace gas levels, but it underestimates hydrogen peroxide mixing ratios at high wind speeds, indicating too-strong dry deposition to the ocean surface. An interesting feature during the cruise is a strong i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 33 publications
3
45
0
Order By: Relevance
“…Previous measurements of methylglyoxal and glyoxal in rural locations have revealed mixing ratios up to a few hundred pptv (see Fu, 2008 for a summary) which were correlated with those of HCHO (Lee et al, 1995) or CO (Spaulding et al, 2003) and which had mixed biogenic and anthropogenic sources. Greatly elevated concentrations of methylglyoxal (> 900 pptv) and glyoxal (> 500 pptv) have been observed in biomass-burning-impacted air masses in a rural environment (Kawamura et al, 2013).…”
Section: Box Model Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous measurements of methylglyoxal and glyoxal in rural locations have revealed mixing ratios up to a few hundred pptv (see Fu, 2008 for a summary) which were correlated with those of HCHO (Lee et al, 1995) or CO (Spaulding et al, 2003) and which had mixed biogenic and anthropogenic sources. Greatly elevated concentrations of methylglyoxal (> 900 pptv) and glyoxal (> 500 pptv) have been observed in biomass-burning-impacted air masses in a rural environment (Kawamura et al, 2013).…”
Section: Box Model Resultsmentioning
confidence: 92%
“…Methylglyoxal is formed at high yield from the OHinitiated oxidation of several biogenic (especially isoprene) and anthropogenic VOCs, e.g. via degradation of aromatic hydrocarbons (Arey et al, 2009;Obermeyer et al, 2009) and is found in biomass-burning-impacted air masses (Fu et al, 2008;Akagi et al, 2011;Stockwell et al, 2015) and those influenced by urban emissions of aromatics (Liu et al, 2010). It is also formed at yields of several percent from the ozonolysis of monoterpenes such as α-Pinene and 3 -carene (Yu et al, 1998;Fick et al, 2003), which were both present at high concentrations during HUMPPA-COPEC-2010.…”
Section: Box Model Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past years, a number of field observations, laboratory studies and modeling research have been carried out to investigate the abundance and behavior of peroxides in the atmosphere Mao et al, 2010;Liang et al, 2013a;Sarwar et al, 2013;Epstein et al, 2014;Fischer et al, 2015;Khan et al, 2015). Hydrogen peroxide (H 2 O 2 ), hydroxymethyl hydroperoxide (HMHP, HOCH 2 OOH), methyl hydroperoxide (MHP, CH 3 OOH) and peroxyacetic acid (PAA, CH 3 C(O)OOH) are generally determined to be the principal peroxide compounds in the troposphere with their concentrations ranging from pptv (parts per trillion by volume) to ppbv (parts per billion by volume) (Lee et al, 2000;He et al, 2010;Zhang et al, 2010Zhang et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…In the boundary layer, both transport and dry deposition play a significant role. Due to a rather invariant boundary layer height over the oceans and small horizontal H2O2 concentration gradients in the marine boundary layer, wet and dry deposition and net photochemical tendencies are the dominant processes affecting the H2O2 concentrations (Fischer et al, 2015). In the continental boundary layer, the situation can be complex, since all processes described in Eq.…”
Section: Ho2 + Ho2 + M → H2o2 + O2 + M (R1)mentioning
confidence: 99%